Witnesses to faith? martyrdom in Christianity and Islam - Wicker, Brian 1929- (Ashgate Publishing Limited, 2006)
Focusing on the issue of suicide bombings, or 'martyrdom operations', this book aims to answer what exactly is meant by 'martyrdom', whether in Islam or Christianity. Muslim and Christian scholars come together to find a common understanding, based on the scriptures and traditions of each faith, of martyrdom in this violent world